Study to evaluate the prevalence, importance, and treatment of women with congenital uterine anomalies - Chan, Yee Yin (2019)
Background Congenital uterine anomalies result from the abnormal formation, fusion, or resorption of Müllerian duct during fetal life. They are present in 1–10% of the unselected population, 2–8% of infertile women, and 5–30% of women with a history of miscarriage. The discrepancy in the prevalence rates are likely to be related to the use of different diagnostic tests and the use of non-standardized classification systems to diagnose these anomalies. These anomalies have long been associated with increased rates of subfertility, miscarriage, preterm delivery, and other adverse fetal outcomes. However, such associations might be artefactual.